2013
DOI: 10.4209/aaqr.2012.07.0195
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Ethylene and Secondary Organic Aerosols Using UV-C254 + 185 nm with TiO2 Catalyst

Abstract: In this investigation we evaluated the feasibility and effectiveness of ozone-producing UV (254 + 185 nm) irradiation and a TiO 2 photocatalyst for degradation of ethylene, which is strongly hydrophobic and does not decompose easily in a humid environment. Tests were performed in a photoreactor (V = 0.55 L) under UV irradiation at various wavelengths (365, 254 and 254 + 185 nm), relative humidities (RH < 1% and RH > 86%), atmospheres (pure N 2 and air), residence times (11-33 sec), initial ethylene concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Additionally, high contents of ethylene might suppress the transmission of 185 nm UV light, thereby reducing the production of the HO ● radicals responsible for ethylene oxidation (Gómez Pacheco et al 2012 , Yao et al 2016 ). These results are in accordance with the work of Chang et al ( 2013 ) where the authors reported a decrease in ethylene percentage removal from 63 to 40% upon increasing initial concentration from 20 to 100 mg/kg. The removal of ethylene by VUV photolysis can be said to be a first-order reaction that is dependent on the initial ethylene concentration.…”
Section: Resultssupporting
confidence: 93%
“…Additionally, high contents of ethylene might suppress the transmission of 185 nm UV light, thereby reducing the production of the HO ● radicals responsible for ethylene oxidation (Gómez Pacheco et al 2012 , Yao et al 2016 ). These results are in accordance with the work of Chang et al ( 2013 ) where the authors reported a decrease in ethylene percentage removal from 63 to 40% upon increasing initial concentration from 20 to 100 mg/kg. The removal of ethylene by VUV photolysis can be said to be a first-order reaction that is dependent on the initial ethylene concentration.…”
Section: Resultssupporting
confidence: 93%
“…This powder shows a dramatic increase in photocatalytic action and increased strength, hardness and cutting efficiency. TiO 2 is an excellent material for photocatalytic applications, such as the remediation of pollutants, water splitting, the destruction of highly toxic molecules, the selective and synthetically redox transformations, the production of hydrogen, and for the conversion of solar energy to electric power [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…[143] The photodegradation of ethylene was studied using UV (254 + 185 nm) irradiation and a TiO 2 photocatalyst. It was observed that using UV irradiation considerably improved the photodegradation of ethylene by Chang et al [144] Jeong et al [145] studied the degradation of NO x and toluene by means of UV-C254 + 185 nm/TiO 2 irradiation and reported that NO x and toluene were effectively degraded to HNO 3 and CO 2 , respectively.…”
Section: Pollutant Type Of Catalyst Reactor Referencesmentioning
confidence: 99%